Estudio comparativo de la polinizacion natural y artificial de la manzana cultivar Ana (Malus sp.) en una región alta de Costa Rica (ING) - Zúñiga, Héctor J.; Baraona, Marcia; Blanco., Fabio A (Uniciencia, 1991)
Comparative study of natural and artificial pollination in trees of the Apple cultivar Anna (Malus sp.). Four pollination treatments were compared on three-year old apple trees of the Anna cultivar, in a high land (1.500 meters above sea level) of Costa Rica. The treatments were as follows: 1. Hand pollination with pollen from Jonathan variety, brought from abroad, 2. Hand pollination with locally collected pollen from Noyle variety (also known as Quintanilla), 3. Natural pollination and 4. Self pollination. The hand pollination treatments surpassed the others as to the number of seeds per fruit and in the effective fruiting rate and yield; moreover, 80% of their fruits were normal in shape, whereas the other treatments showed only 10% of their fruits with that characteristic. Germination tests indicated that 53% of pollen grains from Jonathan variety germinated as compared to 74% for local pollen, wich was in accordance with the latter obtaining a higher number of seeds per fruit and a higher fruiting rate and yield.